Answer: OPTION B.
Step-by-step explanation:
Below are shown some transformations for a function f(x):
1) If [tex]f(x)+k[/tex], the function is shifted up "k" units.
2) If [tex]f(x)-k[/tex], the function is shifted down "k" units.
In this case you have the following function, which you can call f(x):
[tex]y =f(x)= x^2 + 2[/tex]
Based on the transformations explained before, if this function is shifted down 4 units, you know that function obtained g(x) is:
[tex]g(x)= x^2 + 2-4\\\\g(x)= x^2 -2[/tex]
Therefore, the equation that will shift the graph of the function down 4 units, is:
[tex]y= x^2 -2[/tex]